A membrane-bound NAC transcription factor as an integrator of biotic and abiotic stress signals - Seo, Pil Joon (Plant Signal Behav, 2010)
Transcription factors are central components of gene regulatory networks that mediate virtually all aspects of growth and developmental processes in biological systems. The activity of transcription factors is regulated at multiple steps, such as gene transcription, posttranscriptional RNA processing, posttranslational modification, protein-protein interactions, and controlled protein turnover. Controlled activation of dormant, membrane-bound transcription factor (MTF) is an intriguing regulatory mechanism that ensures quick transcriptional responses to environmental fluctuations in plants, in which various stress hormones serve as signaling mediators. NTL6 is proteolytically activated upon exposure to cold and induces expression of the Pathogenesis-Related (PR) genes. The membrane-mediated cold signaling in inducing pathogen resistance is considered to be an adaptive strategy that protects plants against infection by hydrophilic pathogens frequently occurring during cold season. We found that NTL6 also mediates abscisic acid (ABA) regulation of abiotic stress responses in Arabidopsis. NTL6 is proteolytically activated by ABA. Transgenic plants overexpressing a nuclear NTL6 form (35S:6ΔC) exhibited a hypersensitive response to ABA and high salinity in seed germination. Taken together, these observations indicate that NTL6 plays an integrative role in plant responses to both biotic and abiotic stress conditions.